1989
DOI: 10.1080/00986448908940186
|View full text |Cite
|
Sign up to set email alerts
|

Steady State and Dynamic Modelling of a Packed Bed Reactor for the Partial Oxidation of Methanol to Formaldehyde Ii. Experimental Results Compared With Model Predictions

Abstract: Heterogeneous and pseudohomogeneous two-dimensional models are compared to steady state and dynamic experimental data from a packed bed reactor for the partial oxidation of methanol to formaldehyde over an iron oxide-molybdenum oxide catalyst. Highly effective parameter estimation software was used to fit selected model parameters to large sets of experimental data so as to obtain small residuals. Heat transfer parameters which were successful in matching data from experiments without reaction were not capable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…Vortmeyer (1982), Ramkrishna and Arce (1989) and Schwedock et al_ (1989)]. Chandrasekharan and Calderbank (1979), Hofmann (1979Hofmann ( ), L6we (1984 and Schwedock et al (1989) observed that heat transport parameters depend on chemical reaction and they state that models generally predict too high hot-spot temperatures for exothermic reactions if the heat transport relations used are determined under non-reaction conditions. They conclude that heat transport and its parameters, ;teff.r and o~,,, should be increased under reaction conditions, whereas this increase depends on the extent of reaction.…”
Section: Theoretical Backgroundsmentioning
confidence: 99%
“…Vortmeyer (1982), Ramkrishna and Arce (1989) and Schwedock et al_ (1989)]. Chandrasekharan and Calderbank (1979), Hofmann (1979Hofmann ( ), L6we (1984 and Schwedock et al (1989) observed that heat transport parameters depend on chemical reaction and they state that models generally predict too high hot-spot temperatures for exothermic reactions if the heat transport relations used are determined under non-reaction conditions. They conclude that heat transport and its parameters, ;teff.r and o~,,, should be increased under reaction conditions, whereas this increase depends on the extent of reaction.…”
Section: Theoretical Backgroundsmentioning
confidence: 99%
“…The results of these rate equations have been presented before in the figures showing the experimental results (Figs. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. With the derived kinetic model the reaction rates could be well described within typically 5-15% accuracy (deviation).…”
Section: Derivation Of Rate Equationsmentioning
confidence: 99%
“…The experimentally determined steady-state formaldehyde partial oxidation reaction rates have been compared with literature data from Edwards et al [6], Diakov et al [14], Schwedock et al [11] and Dente et al [21]. Although the formaldehyde partial oxidation is the most important consecutive reaction during the partial oxidation of methanol to formaldehyde, relatively few kinetic studies have been carried out to determine the intrinsic reaction rate for this reaction.…”
Section: Comparison Of the Formaldehyde Partial Oxidation Reaction Ramentioning
confidence: 99%
See 2 more Smart Citations